2021
DOI: 10.3390/ijerph18105248
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Artificial Neural Networks to Predict the Physicochemical Characteristics of Water Quality in Three District Municipalities, Eastern Cape Province, South Africa

Abstract: Reliable prediction of water quality changes is a prerequisite for early water pollution control and is vital in environmental monitoring, ecosystem sustainability, and human health. This study uses Artificial Neural Network (ANN) technique to develop the best model fits to predict water quality parameters by employing multilayer perceptron (MLP) neural network and the radial basis function (RBF) neural network, using data collected from three district municipalities. Two input combination models, MLP-4-5-4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…For instance; Bokde et al [52] estimated TDS (mg/L) using SVM, forest (RF), and gradient boosted decision tree (GBDT) and the best accuracy was found within the range of 80-85%. Setshedi et al [53] studied different types of ANN such as multilayer perceptron (MLP) neural network and the radial basis function (RBF) neural network for the physicochemical characteristic of GW in South Africa. The finding indicated the capability of AI-based models but with less accuracy than the current analysis using HW models.…”
Section: Results Of Ai-based Modelsmentioning
confidence: 99%
“…For instance; Bokde et al [52] estimated TDS (mg/L) using SVM, forest (RF), and gradient boosted decision tree (GBDT) and the best accuracy was found within the range of 80-85%. Setshedi et al [53] studied different types of ANN such as multilayer perceptron (MLP) neural network and the radial basis function (RBF) neural network for the physicochemical characteristic of GW in South Africa. The finding indicated the capability of AI-based models but with less accuracy than the current analysis using HW models.…”
Section: Results Of Ai-based Modelsmentioning
confidence: 99%
“…Many endophytic fungal species have been reported to play a vital role in agarwood resin production in the Aquilaria and Gyrinops species [ 23 ]. Table 2 describes the various fungal endophytes known to induce agarwood formation in the Aquilaria and Gyrinops species.…”
Section: Biological Induction and Biosynthesis Of Resinmentioning
confidence: 99%
“…There is also increasing evidence that pericoronary fat inflammation (pFAI) measured in the right coronary artery (RCA) is an independent predictor of cardiovascular events and mortality [ 12 , 13 , 14 , 15 , 16 , 17 ]. In addition, other evidence exists about the role of elevated pFAI in patients with myocarditis, myocardial infarction with nonobstructive coronary arteries (MINOCA) and Takotsubo syndrome [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other evidence exists about the role of elevated pFAI in patients with myocarditis, myocardial infarction with nonobstructive coronary arteries (MINOCA) and Takotsubo syndrome [ 13 , 14 ]. Indeed, pericoronary adipose tissue releases proinflammatory cytokines that can alter the structure of the coronary wall, leading to CAD [ 15 ]. Previous studies indicated that pFAI correlates with plaque attenuation components in patients with non-ST-elevation acute coronary syndrome [ 16 ].…”
Section: Introductionmentioning
confidence: 99%